Alternating North‐South Brightness Ratio of Ganymede's Auroral Ovals: Hubble Space Telescope Observations Around the Juno PJ34 Flyby. Issue 23 (12th December 2022) - Saur, Joachim; Duling, Stefan; Wennmacher, Alexandre; Willmes, Clarissa; Roth, Lorenz; Strobel, Darrell F.; Allegrini, Frédéric; Bagenal, Fran; Bolton, Scott J.; Bonfond, Bertrand; Clark, George; Gladstone, Randy; et al.
Abstract: We report results of Hubble Space Telescope observations from Ganymede's orbitally trailing side which were taken around the flyby of the Juno spacecraft on 7 June 2021. We find that Ganymede's northern and southern auroral ovals alternate in brightness such that the oval facing Jupiter's magnetospheric plasma sheet is brighter than the other one. This suggests that the generator that powers Ganymede's aurora is the momentum of the Jovian plasma sheet north and south of Ganymede's magnetosphere. Magnetic coupling of Ganymede to the plasma sheet above and below the moon causes asymmetric magnetic stresses and electromagnetic energy fluxes ultimately powering the auroral acceleration process. No clear statistically significant timevariability of the auroral emission on short time scales of 100s could be resolved. We show that electron energy fluxes of several tens of mW m −2 are required for its OI 1, 356 Å emission making Ganymede a very poor auroral emitter. Plain Language Summary: Jupiter's moon Ganymede is the largest moon in the solar system and the only known moon with an intrinsic magnetic field and two auroral ovals around its north and south poles. Earth also possesses two auroral ovals, which are bands of emission around its poles. This emission is also referred to as northern and southern lights. We use the Hubble Space Telescope to observe Ganymede's aurora around the time when NASA's Juno spacecraft had a close flyby at Ganymede. We find that the brightness of the northern and southern ovals alternate in intensity with a period of 10 hr. Additionally, we derive that an energy flux of several tens of milli‐Watt per square meter is necessary to power the auroral emission. This energy flux comes from energetic electrons accelerated in the vicinity of Ganymede. Key Points: Hubble Space Telescope observations of Ganymede's orbitally trailing hemisphere on 7 June 2021 in support of Juno flyby Brightness ratio of northern and southern auroral ovals oscillates such that the oval facing the Jovian plasma sheet is brighter Oscillation suggests the aurora is driven by magnetic stresses coupling the moon's magnetic field to the surrounding Jovian plasma sheet